Report of the select committee appointed, on the 10th day of December last to inquire whether any moneys appropriated by Congress for the pay and subsistence of the regular army of the United States, since 4th March, 1815, have been applied to the support of any army or detachment of troops raised without the authority of Congress. (1820)
Summary goes here